2022
DOI: 10.1051/matecconf/202235708005
|View full text |Cite
|
Sign up to set email alerts
|

Wind speed modeling using Weibull distribution: A case of Liptovský Mikuláš, Slovakia

Abstract: In the present paper, the Weibull distribution is used to analyse the wind speed data of Liptovský Mikuláš-Ondrašová (49°05′52″ N, 19°35′32″ E), situated in northern Slovakia. Analysed wind speed data were collected over the 11-year period (2005-2015) and they were recorded three times a day. The results show that the seasonal values of the shape parameter k range from 1.474 to 1.607, with yearly value of 1.546 while the seasonal values of the scale parameter c range from 2.488 to 3.010 m/s, with yearly value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Sedliačková et al [10] have used MLM, which has shown good performance according to root mean square and coefficient of determination values. Another method known as the standard deviation method (SDM) or empirical method of Justus (EMJ) has been used to determine Weibull parameters in Kaplan [11], and it has yielded very good results for estimating the Weibull parameters.…”
Section: Figure 1 Production and Consumption Of Electricity In Saudi ...mentioning
confidence: 99%
“…Sedliačková et al [10] have used MLM, which has shown good performance according to root mean square and coefficient of determination values. Another method known as the standard deviation method (SDM) or empirical method of Justus (EMJ) has been used to determine Weibull parameters in Kaplan [11], and it has yielded very good results for estimating the Weibull parameters.…”
Section: Figure 1 Production and Consumption Of Electricity In Saudi ...mentioning
confidence: 99%